The function and meaning of metaphors in medicine from the perspective of cognitive linguistics - Fabčič, Melanija Larisa; Bernjak, Elizabeta (Anali PAZU HD, 2022)
The cognitivist approach to the theory of metaphor is based on the premise that metaphor is part of the human conceptual system and only secondarily a part of the human language (since language is a reflection of mental processes). Metaphor is therefore an epistemological tool and as such indispensable in science (and its terminology), including medicine. One of the most notable characteristics of the medical discourse is terminology, which has a naming (nominative) as well as a cognitive function. Just like other linguistic expressions terminological expressions are the result of the process of conceptualization and are often based on conceptual metaphors, which undergo a process of verbal symbolization. Based on our analysis of selected examples from medical texts, we postulate a universal presence of metaphors in medical discourse.
Keywords: Cognitive metaphor theory; conceptual metaphor; metaforical expression; medical discourse